Using Dual Criterion Model in the Construction of Teaching Thinking Test among Students of the Departments of Educational and Psychological Sciences - Zahraa Raad Abdul Rasul, Safa Tairq Habeeb (Journal for ReAttach Therapy and Developmental Diversities, 2023)
The present study aims at using dual criterion model in constructing a diagnostic criterion- Referenced test in the course of teaching thinking for the students at the Department of Educational and Psychological Sciences. To achieve this aim, a test of (80) MCQ items with four alternatives has been constructed. The sample of the present study consists of (604) male and female students distributed on the universities of : (Baghdad, Al-Mustansiriya, Al-Iraqya, Al-Kufa, Wasit, Karbala, Al-Qadisiyah). from fourth-grade students in the colleges of education, and for the morning study, for the academic year (2021/2022), The sample was selected by the stratified random method with a proportional distribution. The items have been statistically analyzed by using the (ICL) program in order to grade the items based two-parameter model. The researcher verified the hypothesis of Unidimensionality by using factor analysis by the principal components Kaizer method, and computing the relationship between the item scone and the test total score. In addition, the assumption of freedom from speed factor as well as the decrease of the Guessing factor have been verified through assuring the individuals performance who were of lower ability on the difficult items. As a result, the items have been matched to the assumptions above. To identify the cut-off score of the test, the opposite groups method has been used, where the score has been found out to be (51) representing (68.5%). The assumptions of this model have been verified by the significance of matching all the test items with the model itself except five items which were not matched. The final version of the test consists of (75) items. Result of the data analysis show that all the items and the whole lest have good psychometric characteristics. Based on the results, the researcher reached a set of conclusions, recommendations and suggestions.